Radical-mediated oxidative desulfurization of dibenzothiophene in a chromophore-enhanced photocatalytic system - Park, Jihee; Yi, Jaeseon; Kim, Sujeong; Moon, Gun-hee; Choi, Wonyong (Elsevier BV, 2024)
This study presents a refined photocatalytic oxidative desulfurization (PODS) approach, leveraging a chromophore-enhanced system specifically designed for the selective degradation of dibenzothiophene (DBT). Employing a ruthenium-based complex (RuL) as a model sensitizer that can be activated by visible light, the system catalytically decomposes peroxydisulfate (S2O82-) into highly reactive radical species, key agents in facilitating efficient sulfur oxidation. In this system, the oxidative degradation of DBT proceeds through a well-defined pathway, sequentially transforming DBT into its sulfoxide (DBT-O) and subsequently into its sulfone (DBT-O-2) derivatives, achieving nearly complete conversion to DBT-O-2. The electron transfer dynamics within this photocatalytic system are examined through a concentration-dependent decrease in photoluminescence. Moreover, the effects of various electron donors and acceptors on the system's catalytic activity, as well as the influence of structural modifications of the ruthenium sensitizer are investigated. Comparative evaluations with an alternative 9,10-dicyanoanthracene (DCA)-sensitized system underscore the superior efficiency and selectivity of the sulfate and/or hydroxyl radicals generated in the RuL/S2O82- system. Unlike the superoxide radicals produced in the DCA-sensitized system, the radicals generated in the RuL/S2O82- system exhibit significantly enhanced kinetics for DBT oxidation. The RuL/S2O82- photocatalytic system operates effectively under milder conditions without requiring hydrogen, positioning it as a promising alternative for sulfur removal and potentially contributing to more environmentally sustainable and economically viable fuel processing technologies.